Endodontic management of type I maxillary first molar with two palatal roots using cone-beam computed tomography - Alghamdi, Nuha (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Understanding the anatomical variations in the root canal system is vital for the successful outcome of endodontic treatment. Anatomical variation with respect to palatal roots is rare compared with other roots of maxillary molars. Purpose: This case report describes a rare case of cone-beam computed tomography (CBCT)-guided endodontic treatment of a maxillary first molar with two palatal roots. Case: A 35-year-old Saudi woman complained of continuous pain in the right maxillary first molar. Past dental history revealed root canal treatment of the same tooth four weeks prior. Master cone radiographs recovered from her general dentist revealed a missing second palatal canal. Case Management: A CBCT image was taken to confirm if there were any aberrations in root canal morphology. Clinical exploration presented four distinct orifices: two palatal and two buccal. All the root canals were prepared and irrigated with 2.5% NaOCl and normal saline during instrumentation. All the canals were obturated with gutta-percha and AH 26 sealer using the continuous wave obturation technique. Conclusion: Clinical exploration of the pulpal floor, along with multiple angled radiographs, is needed to confirm any anatomic aberration.